The Association Between Maternal Knowledge, Parenting Style, and Child Feeding Practices with Stunting: A Case-Control Study - Ni Putu Aryani; Eka Adithia Pratiwi; Idyatul Hasanah (An Idea Health Journal, 2026)
Background: Stunting continues to pose a significant public health challenge, especially in low- and middle-income countries. Limited parental knowledge, ineffective parenting styles, and inadequate feeding practices are recognized as key determinants of childhood stunting. This study investigated the associations among parental knowledge, parenting styles, feeding practices, and stunting in children. Methods: A quantitative case–control study was conducted from January to March 2025 in West Lombok Regency, Indonesia, with 350 respondents selected via simple random sampling. The independent variables were parental knowledge, parenting styles, and feeding practices, and the dependent variable was stunting status. Data collection utilized validated and reliable questionnaires. Statistical analyses included univariate descriptive statistics and bivariate analysis using the Chi-square test. Results: The majority of non-stunted children had parents with good knowledge (93.6%), authoritarian parenting styles (58.7%), and appropriate feeding practices (94.1%). Conclusion: Parental knowledge, parenting styles, and feeding practices were significantly associated with stunting.